2018
DOI: 10.1007/s10741-018-9710-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of B-type natriuretic peptide-guided care in patients with heart failure: a systematic review

Abstract: Measuring the level of B-type natriuretic peptide (BNP), as a guide to pharmacotherapy, can increase the survival of patients with heart failure. This study is aimed at systematically reviewing the studies conducted on the cost-effectiveness of BNP-guided care in patients with heart failure. Using the systematic review method, we reviewed the published studies on the cost-effectiveness of BNP-guided care in patients with heart failure during the years 2004 to 2017. The results showed that all studies clearly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…HF is one of the leading causes of morbidity, mortality, and readmission to the hospital. The economic burden of the disease has increased dramatically over the past two decades, leading to the waste of resources and increases in the costs of health care systems [ 56 ]. In the last three decades, pharmaceutical treatments based on current clinical guidelines, including the use of Angiotensin Receptor Blockers, have shown significant success in reducing hospitalization, morbidity, and mortality associated with HF [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…HF is one of the leading causes of morbidity, mortality, and readmission to the hospital. The economic burden of the disease has increased dramatically over the past two decades, leading to the waste of resources and increases in the costs of health care systems [ 56 ]. In the last three decades, pharmaceutical treatments based on current clinical guidelines, including the use of Angiotensin Receptor Blockers, have shown significant success in reducing hospitalization, morbidity, and mortality associated with HF [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Final selected studies in this review reported a wide range of incremental costeffectiveness ratio (ICER). In order to compare different ICER, all of them were inflated by 2020 at an annual rate of 3% [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is uncertainty about the cost effectiveness of BNP testing. A systematic review by Jafari et al (2018) concluded that the use of BNP testing in patients with heart failure may reduce cost compared to the symptom-based clinical care and increase QALY. Treatment of HF should not only take into account cost of treatment but also possible testing for markers such as BNP which may improve cost effectiveness of treatment.…”
Section: Gaps In Studies and Potential For Future Developmentmentioning
confidence: 99%